Judicious Toggling of mTOR Activity to Combat Insulin Resistance and Cancer: Current Evidence and Perspectives - Ong, Pei Shi; Wang, Louis Z.; Dai, Xiaoyun; Tseng, Sheng Hsuan; Loo, Shang Jun; Sethi, Gautam (Frontiers in Pharmacology, 2016)
The mechanistic target of rapamycin (mTOR), via its two distinct multiprotein complexes, mTORC1, and mTORC2, plays a central role in the regulation of cellular growth, metabolism, and migration. A dysregulation of the mTOR pathway has in turn been implicated in several pathological conditions including insulin resistance and cancer. Overactivation of mTORC1 and disruption of mTORC2 function have been reported to induce insulin resistance. On the other hand, aberrant mTORC1 and mTORC2 signaling via either genetic alterations or increased expression of proteins regulating mTOR and its downstream targets have contributed to cancer development. These underlined the attractiveness of mTOR as a therapeutic target to overcome both insulin resistance and cancer. This review summarizes the evidence supporting the notion of intermittent, low dose rapamycin for treating insulin resistance. It further highlights recent data on the continuous use of high dose rapamycin analogs and related second generation mTOR inhibitors for cancer eradication, for overcoming chemoresistance and for tumor stem cell suppression. Within these contexts, the potential challenges associated with the use of mTOR inhibitors are also discussed.